EFFECT OF ECO-FRIENDLY MODIFIED UREA MATERIALS AND NITROGEN LEVELS ON GROWTH AND PRODUCTIVITY OF AROMATIC HYBRID AND AN AROMATIC HIGH YIELDING VARIETY OF RICE - KUMAR, SUNIL; SHIVAY, YASHBIR SINGH (Annals of Agricultural Research, 2014)
A field experiment was carried out to find out the effect of eco-friendly modified urea materials and nitrogen levels on growth and productivity of an aromatic hybrid and aromatic high yielding variety of rice. The treatments consisted of 2 rice varieties (Pusa 1121’ and ’PRH 10’); 4 N levels (0, 50, 100 and 150 kg N/ha) and 3 N sources (prilled urea, neem bitter coated urea and Pusa neem golden urea). The experiment was laid out in factorial randomized block design with 3 replications. The result of this study showed that the significantly higher values of growth parameters viz. tillers/ hill, leaf area index at 30, 60 and 90 days after transplanting and also dry matter accumulation at the same growth stages were recorded with an aromatic hybrid ’PRH 10’ compared to a high yielding aromatic rice variety ’Pusa 1121’. Similar results were also recorded with yield attributes viz. panicles/ m2, panicle weight, panicle length, filled grains/panicle, 1,000-grain weight and also grain and straw yields. With each successive increase in the N levels up to 100 kg/ha, there were significantly increase in the growth parameters, yield attributes and yields of rice. Among the 3 N sources both the modified urea materials i.e. neem bitter-coated urea and Pusa neem golden urea were observed better than prilled urea with rice growth parameters, yield attributes and yields.